Research Progress on Thermal Runaway Warning Methods and Fire Extinguishing Technologies for Lithium-Ion Batteries - Peicheng Shi; Hailong Zhu; Xinlong Dong; Bin Hai (World Electric Vehicle Journal)
Lithium-ion batteries (LIBs), valued for their high energy density, long lifespan, and low environmental impact, are widely used in electric vehicles (EVs) and energy storage. However, increased energy density has exacerbated thermal runaway (TR) issues, hindering large-scale applications. This paper systematically analyzes the mechanisms of TR and strategies for early warning and prevention to enhance battery safety. It begins by detailing TR mechanisms and their triggers, then reviews various TR early warning technologies, fire prevention methods, and the effectiveness and mechanisms of novel extinguishing agents such as hydrogels, perfluorohexanone, liquid nitrogen (LN), dry powder, and aqueous vermiculite dispersion (AVD). The study also explores advancements in new fire-retardant coatings for batteries. Finally, it summarizes current challenges and forecasts future research directions in battery technology. This review offers readers a clear, systematic overview of TR mechanisms, warning systems, and prevention technologies, providing comprehensive insights into TR management.